Urban air pollution and vulnerable area : an alternative approach using remote sensing and GIS : a case study in the city of Colombo, Sri Lanka - Dissanayake, Thamara; Dissanayake, Karunadasa (Saarbrücken : LAP Lambert Academic Publishing, 2011)
Air pollution is a critical problem of urbanization and industrialization all over the world and it has created number of problems in the city of Colombo. It is responsible for eradicating of plants, animals and causing human health problems. The study has examined the spatial variation in NO2 and SO2 concentration pertaining to air pollution and some areas have been identified as vulnerable areas. It is vital to discover spatial distribution pattern of air pollution in urban area and study the vulnerable sites using Remote Sensing (RS) and Geographic Information Systems (GIS). These technologies helped to satellite image analysis and spatial analysis. Very few academic literatures exist on correct usage of these technologies for studies. Traditional methods of data collection have limited access to analyze data and updated information which are vital for urban planners and policy makers. This book will provide information for the new techniques of data collection, updating existing data, exposure of vegetation cover, surface temperature and identification of highest polluted and vulnerable areas of the city which should be valuable to researchers and Professionals in urban planning.
Keywords: Air -- Pollution -- Sri Lanka -- Colombo; Air quality management